Recidivism Prevention Through Prosocial Support: A Systematic Review of Empirical Research - McDaniel, Kimber (2014)
Of the 700 offenders that are released from prison each year, seven in ten will be rearrested. There are a number of barriers face by released offenders that inhibit their successful reentry. These barriers include: mental health illness, limited work experience, lower education, substance abuse, lack of transportation, homelessness and poverty strain of family ties and/or close relationships. This paper explores the impact of social support on recidivism rates through a systematic review of the literature surrounding prosocial support. The implications for social work practice and research are also discussed